5 Jaar Keramiek België - Nederland. - Segers, Karel; Willems, Maxim (Knokke-Heist : Cultureel Centrum Knokke-Heist vzw, 1998)
Abramsen, Per ; Van Geert, Ann ; Vanonna, Paula ; Zaman, André ; De Mits, Trees ; Hoys, Marnix ; Rijk, Ellen ; Van Hoften, Teja ; Pallaghy, Piró ; Speekenbrink, Willem ; Vandewege, Rik ; Wolvers, Henk ; Bosch, Bertine ; Desmedt, Emile ; Van Geert, Johan ; Warringa, Camiela ; Borst, Wim ; Meeuwsen, Hans ; Roos, Anima ; Vanwynsberghe, Dries
Nederlands
boek